Ambivalent Masculinity as Symbolic Violence: Reconfiguring “Honey and Poison” in Eka Kurniawan’s Mat Pisau - Shofah, Novia Adibatus; Fatimah; ’Asyuro, Aniqo Dhamar (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This article examines the construction of ambivalent masculinity in Eka Kurniawan’s Mat Pisau, focusing on the knife as a medium of symbolic violence where power and vulnerability intersect. Studies of masculinity have often emphasized domination and violence, yet tend to overlook the destructive contradictions inherent within it. This article addresses this gap by positioning masculinity not as a stable identity, but as an inherently ambivalent one. The analysis draws on R.W. Connell’s theory of masculinity and Judith Butler’s concept of gender performativity, employing a qualitative approach. It focuses on the actions of the male character Mat Pisau and the female character Emi, their relational dynamics, and the symbolic elements within the text. The findings reveal that the knife functions as both "honey" and "poison"; it not only provides social legitimacy and masculine authority but also produces alienation, emotional repression, and relational destruction. Also, masculinity in the text operates not merely as a dominant force but as a contradictory system that entraps men within cycles of violence against themselves. Theoretically, this study proposes that masculinity can be reinterpreted as an ambivalent construct marked by internal conflict and sustained through symbolic violence.